2020
DOI: 10.1111/1752-1688.12823
|View full text |Cite
|
Sign up to set email alerts
|

A City Wide Assessment of the Financial Benefits of Rainwater Harvesting in Mexico City

Abstract: We assess the potential financial benefits of rooftop rainwater harvesting (RWH) in Mexico City from the perspective of property owners and entrepreneurs. A bottom‐up approach was followed by evaluating RWH at individual buildings and aggregating the results to a borough/city level. We consider sector‐specific water demands, potable and nonpotable uses, and user‐specific water tariffs. We find that RWH is economically most beneficial for nondomestic users rather than for small domestic users, who are often the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…However, when piped water is subsidized, rainwater harvesting is only economically optimal when piped supply is so limited that households must rely on secondary, more expensive water sources. This is consistent with other rainwater harvesting research, which has shown that the economic benefits of rainwater harvesting are highly dependent on municipal water rates. ,, Since piped water is often heavily subsidized, either directly or through government-funded infrastructure projects, a comparison to the price of subsidized piped water minimizes the value of rainwater, especially in areas with robust water supply and infrastructure . Additionally, rainwater harvesting may provide many community-wide co-benefits (e.g., decreased pressure on strained water supplies, flood reduction , ) not considered in our model.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…However, when piped water is subsidized, rainwater harvesting is only economically optimal when piped supply is so limited that households must rely on secondary, more expensive water sources. This is consistent with other rainwater harvesting research, which has shown that the economic benefits of rainwater harvesting are highly dependent on municipal water rates. ,, Since piped water is often heavily subsidized, either directly or through government-funded infrastructure projects, a comparison to the price of subsidized piped water minimizes the value of rainwater, especially in areas with robust water supply and infrastructure . Additionally, rainwater harvesting may provide many community-wide co-benefits (e.g., decreased pressure on strained water supplies, flood reduction , ) not considered in our model.…”
Section: Resultssupporting
confidence: 87%
“…This study, and others like it, could be strengthened by larger scale household data collection, and particularly detailed data collection around household water consumption, that would allow for an investigation of where households would fall on the presented trade-off curves. Important input data, such as number of people per household, rainfall depth, and household roof area, often vary widely across the city, contributing to the variability of water scarcity across small distances and brief time periods; a system-wide analysis must consider this heterogeneity. Optimal interventions for households can be explored by comparing Pareto fronts for different scenarios and identifying ones that allow for the lowest costs at high reliability; a minimum volume of piped water and sufficient storage are important for reducing costs for households.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Central Bank 2021). The runoff surface coe cient was set to 0.8 and an initial water discharge of 2 mm was applied (recommended in the NBR 15527) in the case of three consecutive dry days (with less than 1 mm of rainfall) (Larrauri et al 2020). The selection of the ideal volume for the lower reservoir was based on the e ciency criteria de ned as the rate between the increase in the supplied water from the RWHS per increase in the reservoir volume.…”
Section: Other Accessories Inspectionmentioning
confidence: 99%
“…O programa inicialmente efetua uma simulação contínua do balanço hídrico considerando o método do consumo de água depois do enchimento do reservatório (Yeld After Spillage -YAS), que proporciona resultados mais conservadores (FEWKES e BUTLER, 2000;MITCHELL, 2007). Foi adotado um descarte inicial de 2 mm, recomendado pela NBR 15527 (ABNT, 2019), quando há ao menos três dias consecutivos sem precipitação (precipitação inferior a 1 mm), conforme Larrauri et al (2020).…”
Section: Avaliação Do Desempenho Dos Saapunclassified